Ant colony optimization (ACO) technique for reactive power planning in power system stability assessment / Mohd Rozely Kalil - Kalil, Mohd Rozely (2008)
This thesis presents Ant Colony Optimization (ACO) Technique for Reactive Power Planning in Power System Stability Assessment. ACO is a new cooperative agent’s approach, which is inspired by the observation of the behaviours of real ant colonies on the topics of ant trial formation and foraging method. The set of cooperating agents called “ant” cooperate to find good solution for voltage stability studies in power system. This study involved the development of ACO technique for estimating optimal maximum loadability (OML), optimal reactive power dispatch (ORPD), optimal transformer tap changer setting (OTTCS) and optimal reactive power planning (ORPP) in power system. The ACO algorithm is written in MATLAB and tested on IEEE 30-bus Reliability Test System (RTS) in order to verify the proposed technique. Comparative studies were also conducted between the results obtained from the proposed techniques with those obtained by previously developed techniques. The OML technique was used to find the maximum reactive power loading at particular load bus before the system become unstable. The purpose of ORPD, OTTCS and ORPP technique in reactive power planning (RPP) study is mainly to improve the voltage profile or to minimize transmission losses in the system. The ORPD is implemented to the system by injecting reactive power to the generator buses, while OTTCS aimed to modify the transmission line parameters in order to improve voltage profile and also to reduce total loss in the system. The ORPP has been conducted by combining ORPD and OTTCS which provided better result in terms of voltage profile improvement and total loss minimization at loaded bus.